Oxidative stress, inflammation and the metabolic EpOME are associated with occupational exposure to isoflurane - Silva, Mariane Aparecida Pereira [UNESP]; Grassi, Tony Fernando [UNESP]; Mur, Luis A J; Zainurin, Nur Aimi A; Beckmann, Manfred; Souza, Hendrew Jesus Barbosa Campos de [UNESP]; Destro, Maria Vitória [UNESP]; Damasceno, Débora Cristina [UNESP]; Corrêa, Camila Renata [UNESP]; Golim, Marjorie de Assis [UNESP]; Ferrari, Renata; Marcondes, João Paulo C; et al. (Elsevier, 2025)
This study assessed the occupational exposure to the waste anesthetic gas (WAG) isoflurane in veterinarians focusing on oxidative stress and inflammatory markers in addition to metabolomic profiling. This was a case-control study with matched individuals related to dosimeter data for WAG. Systemic oxidative stress markers (malondialdehyde, 8-iso-prostaglandin F2α and carbonylated proteins) were screened, as well as carbonylated protein degradation products and 8-hydroxydeoxyguanosine in urine. Cholesterol and fractions were also assessed. Antioxidant enzymes were evaluated in washed red blood cells, while antioxidant capacity was evaluated in plasma. Primary and oxidative DNA damage were assessed using comet assays. Inflammatory markers were detected via flow cytometry. Untargeted metabolomics were evaluated in plasma by flow infusion electrospray ionization high-resolution mass spectrometry (FIE-MS). Dosimeter data indicated high-level of WAG exposure by veterinarians which was associated with elevated lipid and protein oxidations as well as DNA damage (primary lesions and oxidized pyrimidines). The antioxidant response showed reduced superoxide dismutase and elevated glutathione peroxidase activities. Inflammatory profiling revealed higher levels of IL-8, IL-12p70, IL-17A, IL-18, and IL-23 in the exposed group. Metabolomic analysis revealed a distinct metabolite signature in exposed individuals with perturbations in lipid (linoleic, alpha-linolenic, and arachidonic acid pathways), glutathione metabolism and ubiquinone, aligning with the observed oxidative and inflammatory profiles. In addition, we targeted an epoxyoctadecenoic acid (EpOME) with an area under the curve value of 1.0 that was related to anesthetic occupational exposure. These integrative findings demonstrate that high-level of occupational exposure to the WAG isoflurane is associated with systemic biological disruptions involving oxidative stress, inflammation, and lipid metabolic dysregulation.